Pilea microphylla (L.) Liebm. (Urticaceae) and Solidago canadensis L. (Asteraceae): First Report of Naturalized Status in Nepal - Poudel, Yogendra Bikram; Poudel, Suman; Adhikari, Bhaskar; Paudyal, Som Prasad; Shrestha, Bharat Babu (Nepal Journal of Botany, 2025)
Two herb species, Pilea microphylla (L.) Liebm. (Urticaceae) and Solidago canadensis L. (Asteraceae), are reported as naturalized for the first time in Nepal. Voucher specimens of these plants were collected from different parts of Nepal including Kathmandu valley. A detailed description with taxonomic notes, distinguishing characters, habitat, distribution and color photographs of the species are provided. In addition, the morphological characters of these plants are compared with their allied species. The potential for these species to become invasive is also briefly discussed.